1997
DOI: 10.1111/j.1365-246x.1997.tb06601.x
|View full text |Cite
|
Sign up to set email alerts
|

On the resolution of the isotropic component in moment tensor inversion

Abstract: S U M M A R YIt is in theory possible to solve a full moment tensor from inversion of a few seismograms, using normal-mode data, surface waves or body waves. In fact, the isotropic component is usually set to zero in many inversions, in order to stabilize them. This approximation may be considered valid for tectonic earthquakes, but for other applications (such as the study of nuclear or volcanic explosions, deep earthquakes and induced seismicity), the determination of the volumetric component is a key point … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
88
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(90 citation statements)
references
References 34 publications
2
88
0
Order By: Relevance
“…A discussion of the isotropic part of the moment tensor must include the possibility that it is an artifact, because it appears to be the most poorly resolved part of the moment tensor. Discussions of this matter can be found in O' CONNELL and JOHNSON (1988), VASCO and JOHNSON (1989), KUGE and LAY (1994), Š ILENÝ et al (1996), (2009), DUFUMIER and RIVERA (1997), JULIAN et al (1998) andCOVELLONE andSAVAGE (2012). This possibility of a greater uncertainty in the isotropic part is supported by the results listed in Table 7, wherem iso is considerably smaller than m o , but sd½m iso is only slightly smaller than sd[m o ].…”
Section: General Resultssupporting
confidence: 76%
“…A discussion of the isotropic part of the moment tensor must include the possibility that it is an artifact, because it appears to be the most poorly resolved part of the moment tensor. Discussions of this matter can be found in O' CONNELL and JOHNSON (1988), VASCO and JOHNSON (1989), KUGE and LAY (1994), Š ILENÝ et al (1996), (2009), DUFUMIER and RIVERA (1997), JULIAN et al (1998) andCOVELLONE andSAVAGE (2012). This possibility of a greater uncertainty in the isotropic part is supported by the results listed in Table 7, wherem iso is considerably smaller than m o , but sd½m iso is only slightly smaller than sd[m o ].…”
Section: General Resultssupporting
confidence: 76%
“…If the sources are located at shallow depths with respect to the wavelength used in the inversion, the isotropic part of the moment tensor cannot be fully recovered (Dufumier and Rivera, 1997;Julian et al, 1998). In the present study this likely introduced errors in isotropic moments such as artificial negative volumetric changes for the double-couple sources of surface cluster B.…”
Section: Limitations Of Inversion Schemesmentioning
confidence: 78%
“…It has been shown that care is needed in evaluating the robustness and stability of non-DC and full moment tensor solutions (e.g., Dufumier and Rivera, 1997;Dreger et al, 2000;Vavrycuk, 2001Vavrycuk, , 2011Templeton and Dreger, 2006;Minson et al, 2007;Ford et al, 2008Ford et al, , 2009Ford et al, , 2010). We applied a systematic procedure for the evaluation of aleatoric and epistemic solution uncertainty of seismic moment tensor solutions, using bootstrap, jackknife, and NSS approaches to develop solutions that can be used to investigate the underlying mechanical and fluid-mechanical processes that result in the observed seismicity in The Geysers geothermal field.…”
Section: Discussionmentioning
confidence: 99%